Methodological factors in determining risk of dementia after transient ischemic attack and stroke - Pendlebury, S; Klaus, S; Thomson, R; Mehta, Z; Wharton, R; Rothwell, P (American Stroke Association, 2015)
Cognitive assessment is recommended after stroke but there are few data on the applicability of short cognitive tests to the full spectrum of patients. We therefore determined the rates, causes, and associates of untestability in a population-based study of all transient ischemic attack (TIA) and stroke.Patients with TIA or stroke prospectively recruited (2002-2007) into the Oxford Vascular Study had ≥1 short cognitive test (mini-mental state examination, telephone interview of cognitive status, Montreal cognitive assessment, and abbreviated mental test score) at baseline and on follow-up to 5 years.Among 1097 consecutive assessed survivors (mean: age/SD, 74.8/12.1 years; 378 TIA), numbers testable with a short cognitive test at baseline, 1, 6, 12, and 60 months were 835/1097 (76%), 778/947 (82%), 756/857 (88%), 692/792 (87%), and 472/567 (83%). Eighty-eight percent (331/378) of assessed patients with TIA were testable at baseline compared with only 46% (133/290) of major stroke (P<0.001). Untestability was also associated with older age, premorbid dependency, death on follow-up, and with both pre- and postevent dementia (all P<0.01). Untestability (and problems with testing) were commonly caused by acute stroke effects at baseline (153/262 [58%]: dysphasia/anarthria/hemiparesis=84 [32%], drowsiness=58 [22%], and acute confusion=11 [4%]), whereas sensory deficits caused relatively more problems with testing at later time points (24/63 [38%] at 5 years).Substantial numbers of patients with TIA and stroke are untestable with short cognitive tests. Future studies should report data on untestable patients and those with problems with testing in whom the likelihood of dementia is high.